Photostimulated etching of germanium chalcogenide films - Dan’ko, V.A.; Indutnyi, I.Z.; Myn’ko, V.I.; Shepeliavyi, P.E.; Lukyanyuk, M.V.; Litvin, O.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
The new effect of photostimulated dissolution of as-evaporated and annealed Ge-based chalcogenide glass (ChG) films was investigated in detail. The etching rate increases with the illumination intensity, and its spectral dependence is correlated with absorption in the film at the absorption edge. A possible mechanism for the photoinduced etching of ChG films has been discussed. The high-frequency diffraction gratings on germanium ChG – more environmentally acceptable compounds than traditionally used arsenic chalcogenides – were recorded using the method of interference immersion photolithography with photoinduced etching.